Ketepatan Shooting Petanque : Koordinasi dan Konsentrasi - Habibah Habibah; Rachmat Hidayat; Arman Bin Anuar; A Heri Riswanto (Universitas Hamzanwadi, 2025)
Shooting accuracy is a determining factor in pétanque, which is influenced by various aspects, including hand-eye coordination and concentration. However, many athletes still experience difficulties in shooting accuracy due to weaknesses in these two factors. This study aims to analyze the relationship between hand-eye coordination and concentration on the shooting accuracy of pétanque athletes. The research method used a quantitative approach with a correlation design. The research sample consisted of 15 athletes, comprising 10 males and 5 females aged 18–24 years, selected using saturated sampling techniques. The instruments used included a hand-eye coordination test (throwing a ball at a target for 30 seconds), a concentration test (Nelson Reaction Test), and a shooting accuracy test. Data analysis used the Product Moment correlation test at a significance level of 0.05. The results showed that: (1) there was a significant relationship between hand-eye coordination and shooting accuracy with a value of r = 0.831; (2) there is a significant relationship between concentration and shooting accuracy with a value of r = 0.916; and (3) there is a simultaneous significant relationship between hand-eye coordination and concentration on shooting accuracy with a value of r = 0.959. The conclusion of this study is that eye-hand coordination and concentration have a strong and significant relationship with shooting accuracy, both partially and simultaneously.